Guidance for the assessment of detoxification processes in feed - EFSA Panel on Contaminants in the Food Chain (CONTAM); Dieter Schrenk; Margherita Bignami; Laurent Bodin; James Kevin Chipman; Jesus delMazo; Bettina Grasl‐Kraupp; Laurentius(Ron) Hoogenboom; Jean‐Charles Leblanc; Carlo Stefano Nebbia; Elsa Nielsen; Evangelia Ntzani; et al. (EFSA Journal, 2024)
Abstract This statement provides scientific guidance on the information needed to support the risk assessment of the detoxification processes applied to products intended for animal feed in line with the acceptability criteria of the Commission Regulation (EU) 2015/786.